The Utilization of Artificial Intelligence in Digital Da’wah Content Management: A Case Study of the Instagram Account @my.binjai / Pemanfaatan Artificial Intelligence Dalam Pengelolaan Konten Dakwah Digital Pada Akun Instagram @my.binjai - Muhammad Aziz Mahyuti; Hasnun Jauhari Ritonga (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2026)
This study analyzes the utilization of Artificial Intelligence (AI) in digital da’wah content management on the Instagram account @my.binjai managed by the Muslim Youth Binjai community. The focus of this study is to examine how AI is used in producing and managing da’wah content through ChatGPT and AI features in Canva. This study employed a qualitative approach, with data collected through in-depth interviews, observation, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that @my.binjai has implemented da’wah management functions, including planning, organizing, directing, supervising, and evaluation. AI was used as a supporting tool for idea generation, initial caption drafting, and visual design references. However, verification and editing were still carried out by the content managers to ensure that the messages remained aligned with Islamic values. This study concludes that AI functions as a supporting technology that improves the efficiency of digital da’wah content production without replacing the human role